Pelecehan Seksual Verbal : Adakah peran Intensitas Menonton Film Porno ? - Damayanti, Roisa; Sukiatni, Dwi Sarwindah; Kusumandari, Rahma (Research Journal of Social Science and Economics, 2025)
ABSTRACT The intensity behavior of watching porn movies can increase sexual stimulation which can affect how a person’s attitude and behavior in which these attitudes and behavior can lead to a tendency to verbal sexual harassment behavior. This study aims to determine the relationship between the intensity of watching pornographic films and the tendency for verbal sexual harassment behavior in male students. The method used is quantitative with correlational studies. Sampling used is non-probability sampling with Accidental Sampling Technique. The participants used in this study were 154 male students in Surabaya. The data collection method uses a Likert scale. The measurement tools used are the Intensity of Watching Porn Films scale and the Verbal Sexual Harassment scale. Hypothesis testing in this study used Spearman’s Rho correlation using SPSS. The results of data analysis showed that the Rho value of = 0.798 with a significance of p = 0.000 (p <0.01) so that there was a positive relationship between the intensity of watching porn movies and the tendency of verbal sexual harassment behavior in male students. ABSTRAK Perilaku intensitas menonton film porno dapat meningkatkan rangsangan seksual yang dapat mempengaruhi bagaimana sikap dan perilaku seseorang yang dimana sikap dan perilaku tersebut dapat menimbulkan terjadinya kecenderungan perilaku pelecehan seksual verbal. Penelitian ini bertujuan untuk mengetahui hubungan intensitas menonton film porno dengan kecenderungan perilaku pelecehan seksual verbal pada mahasiswa laki-laki. Metode yang digunakan adalah kuantitatif dengan studi korelasional. Pengambilan sampel yang digunakan adalah non-probability sampling dengan Teknik Accidental Sampling. Partisipan yang digunakan dalam penelitian ini sebanyak 154 mahasiswa laki-laki di Surabaya. Metode pengumpulan data menggunakan skala likert. Alat ukur yang digunakan adalah skala intensitas Menonton Film Porno dan skala Pelecehan Seksual Verbal. Pengujian hipotesis dalam penelitian ini menggunakan korelasi Spearman’s Rho dengan menggunakan SPSS. Hasil analisis data menunjukkan nilai Rho sebesar = 0, 798 dengan signifikasi p=0,000 (p < 0,01) sehingga ada hubungan positif antara intensitas menonton film porno dengan kecenderungan perilaku pelecehan seksual verbal pada mahasiswa laki-laki.